KESULITAN SISWA MENYELESAIKAN SOAL MENGENAI JARAK DALAM BANGUN RUANG BERDASARKAN MODEL KESULITAN NEWMAN - Syafiudin, Muhamad Arif; Hartoyo, Agung; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to know and describe students difficulties in solving problems about distance in solid geometry based on the Newman’serror model in high school